Gangguan Siklus Menstruasi - Alghani, Sulthan Rafi; Sari, Ratna Dewi Puspita; Septiani, Linda; Utama, Winda Trijayanthi (CV. Jasa Sukses Abadi, 2024)
The female reproductive system undergoes regular cycles in preparation for pregnancy and fertilization, known as the menstrual cycle. This cycle involves hormonal changes and complex physiological processes, with the follicular phase dominated by estrogen and the luteal phase dominated by progesterone. Menstrual cycle disorders, such as amenorrhea, polymenorrhea, and oligomenorrhea, can be caused by various factors including hormonal imbalances, unhealthy lifestyles, and certain medical conditions. Management of menstrual disorders varies depending on their causes, which may require a holistic and individualized approach. A good understanding of the menstrual cycle and its disorders is crucial for accurate diagnosis and appropriate treatment. It is also important to promote overall women's reproductive health.